KONTROWERSJE WOKÓŁ URZĘDÓW I URZĘDNIKÓW MIASTA RZYMU - Kamińska, Renata (Zeszyty Prawnicze, 2016)
CONTROVERSIES CONCERNING THE OFFICES AND MAGISTRATES OF THE CITY OF ROME Summary The offices of the curatores were one of the most characteristic elements of public administration during the Principate. Their origins go back to the Republic, when the magistrates responsible for administration and supervision in the city of Rome were the aediles and censors. Augustus, the first emperor, institutionalised the offices of the curatores responsible for particular sectors of the urban administration. The powers and careers of some of the Roman magistrates have been described by Katarzyna Kapłoniak in her book entitled Urzędy kuratorskie administracji miejskiej Rzymu od Augusta do Dioklecjana. Ich miejsce i znaczenie w senatorskim ‘cursus honorum’, published in 2014. In my article I refer to this book and engage in polemic with its author.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />